Changes in forest structure modify understory and livestock occurrence along the natural cycle and different management strategies in Nothofagus antarctica forests - Martínez Pastur, Guillermo José; Cellini, Juan Manuel; Chaves, Jimena Elizabeth; Rodríguez‑Souilla, Julián; Benítez, Julieta; Rosas, Yamina Micaela; Soler Esteban, Rosina Matilde; Lencinas, María Vanessa; Peri, Pablo Luis (Springer Nature, 2022)
Sustainable forest management is proposed as a solution for many ecological and socioeconomic trade-offs associated with different forest uses. In Patagonia, silvopastoral systems were proposed to balance provisioning ecosystem services and other natural values. However, the design of these practices needs a better understanding of livestock production. The objective of this study was to determine changes in the understory forage value and livestock occurrence in Nothofagus antarctica forests of Tierra del Fuego (Argentina) growing under a natural dynamic and in stands with impacts generated by harvesting, fires and silvopastoral uses. We sampled 145 areas determining forest structure, understory forage value (cover, biomass, forage quality) and livestock occurrence (wild and domestic stocking rate), including different forest conditions: (i) six phases of the natural forest cycle (even- and uneven-aged stands), (ii) four types of management and conversion alternatives (different thinning intensities, clear-cuts, and fires), and (iii) three associated environments (forest edges and grasslands). Main results showed that understory cover and biomass did not differ along the natural forest phases, but varied across management alternatives and associated environments. The magnitude of these changes was directly related to the impact degree. Forage quality did not change across the factors and levels. Livestock occurrence is related to the observed changes in the understory; however, a different behaviour was observed between wild and domestic herbivores. The different analyses highlighted the similarities in forage value and livestock occurrence among the different natural forest phases, and showed how the stands with different impacts differed from the control stands. The outputs could be used to improve forest management strategies in the framework of silvopastoral systems at landscape level.